Let's solve the equation step by step. The original equation is:
\[ \frac{3}{4}x + 3 - 2x = -\frac{1}{4} + \frac{1}{2}x + 5 \]
You mentioned that you've already combined terms, so let's start by simplifying both sides.
Step 1: Simplify Both Sides
First, simplify the left side:
\[ \frac{3}{4}x - 2x + 3 \]
To combine \(\frac{3}{4}x\) and \(-2x\), convert \(-2x\) into a fraction with a denominator of 4:
\[ -2x = -\frac{8}{4}x \]
Now combine them:
\[ \frac{3}{4}x - \frac{8}{4}x + 3 = -\frac{5}{4}x + 3 \]
So, the left side simplifies to:
\[ -\frac{5}{4}x + 3 \]
Now, simplify the right side:
\[ -\frac{1}{4} + \frac{1}{2}x + 5 \]
Transform \(5\) into a fraction:
\[ 5 = \frac{20}{4} \]
Combine the constants:
\[ -\frac{1}{4} + \frac{20}{4} = \frac{19}{4} \]
So, the right side simplifies to:
\[ \frac{1}{2}x + \frac{19}{4} \]
Step 2: Combine the simplified expressions
Now we can rewrite the equation as:
\[ -\frac{5}{4}x + 3 = \frac{1}{2}x + \frac{19}{4} \]
Step 3: Clear the fractions
To eliminate the fractions, we can multiply the entire equation by 4 (the common denominator):
\[ 4 \left(-\frac{5}{4}x\right) + 4(3) = 4\left(\frac{1}{2}x\right) + 4\left(\frac{19}{4}\right) \]
This gives:
\[ -5x + 12 = 2x + 19 \]
Step 4: Move all terms involving \(x\) to one side and constants to the other side
\[ -5x - 2x = 19 - 12 \]
Simplifying gives:
\[ -7x = 7 \]
Step 5: Solve for \(x\)
Divide both sides by -7:
\[ x = -1 \]
Final Answer
Thus, the solution to the equation is:
\[ x = -1 \]